2018
DOI: 10.1590/1679-78254327
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation in cellular locally resonant metamaterials

Abstract: Locally resonant acoustic metamaterials have recently attracted a great interest due to their dynamic behaviour, characterized by a band gap at relatively low frequencies. This paper provides a numerical study, by means of finite element modal analyses, of the dynamic properties of 1D mass-inmass and 2D cellular locally resonant metamaterials. The 2D metamaterial is constituted by a cellular metallic lattice, filled by a soft light material with heavy inclusions or resonators. The influence of material paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Various examples of LRM have been reported in the literature, they can be constituted by a periodic structure, made of a single material, with local resonators within the unit cell [12], by three components (e.g. hard inclusions with a soft coating embedded in a hard matrix [16,15] or cellular materials filled by a foam with hard inclusions [10]) or by two materials, typically soft inclusions in hard matrix, as studied e.g. in [22,14].…”
Section: Introductionmentioning
confidence: 99%
“…Various examples of LRM have been reported in the literature, they can be constituted by a periodic structure, made of a single material, with local resonators within the unit cell [12], by three components (e.g. hard inclusions with a soft coating embedded in a hard matrix [16,15] or cellular materials filled by a foam with hard inclusions [10]) or by two materials, typically soft inclusions in hard matrix, as studied e.g. in [22,14].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is due to the local resonance of some portions of the metamaterial which can trap the energy and attenuate wave propagation. Typically, LRM have a periodic or quasi-periodic structure consisting of a single material with local resonators inside the unit cells [14]; two-components materials, as studied, e.g., in [11,19,26]; or three components materials [10,12,21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Such a scheme has been adopted for the mitigation of blast and impact effect, with encouraging results: the Authors of [21] have shown the results of a parametric study on the basis of a mathematical model; a practical implementation of such a concept can be found in [22], that contains also an experimental validation. In the framework of impact absorbers for crash-worthiness of lightweight cars, Comi and Driemeier [23,24] have proposed the adoption of a LRM with a different scheme: a square lattice of aluminium cells, filled by a polymeric foam, with circular lead inclusions. In that case, the study was focused on materials having two-dimensional periodicity and composed of long extruded cells that can be effectively studied by means of plane models considering propagation of pure transverse waves and planar waves separately .…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper is twofold. Firstly, the attention is focussed on the LRM with 2D periodicity, proposed in [24]. Such a metamaterial is characterized by an innovative design and shows the interesting property of overlapping band-gap for in-plane and transverse waves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation